Determining rates of smoking cessation advice delivered during hospitalisation and smoking cessation rates 3 months post discharge: a two-hospital survey. Issue 1 (1st January 2016) - Mellon, Lisa; McElvaney, Noel G.; Cormican, Liam; Hickey, Anne; Conroy, Ronan; Ekpotu, Lenin; Oghenejobo, Oroghene; Atteih, Samar; McDonnell, Ronan; Doyle, Frank
ABSTRACT: Background: Hospitalisation is an ideal time to implement smoking cessation interventions. However, little is known about the extent to which inpatients receive such advice, or the impact it has on motivation to quit and quitting behaviours post-hospitalisation. Aims: This study aimed to determine the prevalence of smoking and cessation advice received by inpatients in two teaching hospitals in Ireland, and the impact of cessation advice on smoking at 3 months post discharge. Methods: We surveyed 1001 inpatients across two hospital sites, over a six-month period. Demographic details, clinical history, smoking history, motivation to quit, cigarette dependence, and recent quitting history were assessed. Results: Prevalence of smoking within the sample was 23.4% (235/1001). Only 32% (75/235) of smokers reported that smoking cessation was discussed during admission. Smokers' mean Fagerström nicotine-dependence score was 3.7 (SD = 2.7), indicating low dependence levels. At 3 months, 17% (25/146) of smokers reported smoking cessation. Provision of smoking cessation advice during hospitalisation was associated with higher motivation to quit (OR = 2.79, 95% CI 2.12–3.68), and successful quit behaviour for confirmed (OR = 1.98, 95% CI 1.55–2.53) and self-reported quitters (OR = 1.47, 95% CI 1.3–1.66) Conclusions: This observational study finds that provision of brief cessation advice and smoking status documentation was suboptimal. Where advice was given, it was associated with enhanced motivation to quit and increased quit rates. These findings, along with low dependence scores, suggest that systematic provision of low-intensity cessation interventions could significantly enhance quit rates in hospitalised smokers.